2021
DOI: 10.1016/j.ijrobp.2020.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness Research in Localized Prostate Cancer: A 10-Year Follow-up Cohort Study

Abstract: Long-term comparative effectiveness research on localized prostate cancer treatments is scarce, and evidence is lacking especially for brachytherapy. The aim of this study was to assess the long-term impact of the side effects of radical prostatectomy, brachytherapy, and external radiation therapy on patients with localized prostate cancer at 10 years, using propensity score analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Acute complications and patient-reported outcomes are also included in ICHOM’s recommendations 31 . The results on survival and biochemical recurrence of the present study need to be balanced with results on patient-reported outcomes previously published 16 , showing that brachytherapy is the treatment option that causes the least negative impact. However, no single treatment can be considered the preferred strategy for managing all patients, and each treatment decision should be made jointly by patients and physicians 5 .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Acute complications and patient-reported outcomes are also included in ICHOM’s recommendations 31 . The results on survival and biochemical recurrence of the present study need to be balanced with results on patient-reported outcomes previously published 16 , showing that brachytherapy is the treatment option that causes the least negative impact. However, no single treatment can be considered the preferred strategy for managing all patients, and each treatment decision should be made jointly by patients and physicians 5 .…”
Section: Discussionmentioning
confidence: 61%
“…Study details have been described elsewhere 13 16 . Briefly, participants in the “Multicentric Spanish Study of Clinically Localized Prostate Cancer” were consecutively recruited from ten Spanish hospitals in 2003–2005.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations